“Revisión del Protocolo de Manejo de la Técnica “Build Up” Para la Rehabilitación de Incisivos Centrales Maxilares Tratados Endodónticamente. Revisión de la Literatura” - Moreno Naranjo, Fernando Sebastián (2024)
The objective of this research project is to evaluate the effectiveness of the 'Build Up' technique for the rehabilitation of endodontically treated maxillary central incisors, with a particular focus on comparing it to traditional methods, such as the use of fiber posts. In order to achieve this objective, an exhaustive review of scientific studies and documented clinical cases exploring the 'Build Up' technique in this context was conducted. The methodology includes a detailed review of the available literature. Specifically, the study is conducted using certified Boolean operators (Decs-Mesh): Composite AND Non-vital teeth, Post less AND resin, build up AND dental core, focusing on the biomaterials used, the adhesion techniques employed and the biomechanical, and aesthetic outcomes achieved. The analysis was conducted through a critical evaluation of academic publications and clinical case reports. Consequently, the results indicate that the 'Build Up' technique is effective for the preservation of dental tissue, providing better adhesion and a more adequate distribution of occlusal forces. This improvement translates into improved durability and aesthetics of restorations, as well as a reduced risk of fracture compared to glass fiber posts. In conclusion, this study suggests that the Build Up technique offers significant advantages in terms of tissue preservation, adhesion and aesthetics and recommends its incorporation into clinical practice